A Risk Management Approach for Software Product Line Engineering - Lobato, Luanna; Bittar, Thiago (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2015.5834, 2015)
Software Product Line (SPL) Engineering is a software development paradigm that fosters systematic reuse. It is focused on improving software practices, leading companies to experience benefits, such as reduced time-to-market and effort, and higher quality for the products delivered to customers. However, establishing a SPL is neither a simple nor a cheap task, and may affect several aspects of a software company. Besides, it involves a range of risks that may hinder project success. These have to be managed accordingly, so as to minimize the likelihood of project failure. Despite the importance of Risk Management (RM) for SPL Engineering, little has been published in terms of suitable and structured practices to cope with that. This present paper reports an approach for RM in SPL Engineering, named RiPLERM (Rise Product Line Engineering – Risk Management). The approach presents activities to structure RM in SPL projects, The design of the RiPLE-RM approach elaborated on results from empirical investigations, and was proposed to facilitate the management and provide significant insights that can be used to avoid and solve risks.